2012
DOI: 10.1111/j.1540-8167.2012.02436.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Anxiety and Depression on the Recurrence of Paroxysmal Atrial Fibrillation After Circumferential Pulmonary Vein Ablation

Abstract: CPVA can ameliorate anxiety and depression, which may contribute to improvement of quality of life in patients with paroxysmal AF. Anxiety and depression increase the recurrence risk of AF after CPVA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 48 publications
(68 reference statements)
3
38
0
Order By: Relevance
“…Although several possible mechanisms have been suggested, such as correlation with systemic inflammation and elevated sympathetic tone, the mechanisms behind this relationship remain unclear. Both anxiety and depression improved after RFA, which is in line with previous studies …”
Section: Discussionsupporting
confidence: 92%
“…Although several possible mechanisms have been suggested, such as correlation with systemic inflammation and elevated sympathetic tone, the mechanisms behind this relationship remain unclear. Both anxiety and depression improved after RFA, which is in line with previous studies …”
Section: Discussionsupporting
confidence: 92%
“…Treatment strategy was determined by participant and electrophysiologist preference . The same study also found participants with higher levels of anxiety and depression to have more AF recurrence at follow‐up after CPVA . A second study found greater improvement in depression, anxiety, and quality of life among 166 participants with paroxysmal AF using catheter ablation over antiarrhythmic drugs .…”
Section: Discussionmentioning
confidence: 90%
“…A recent study of 210 participants with paroxysmal AF found a reduction in anxiety and depression and an increase in quality of life following circumferential pulmonary vein isolation (CPVA) over AF treated with antiarrhythmic medications. Treatment strategy was determined by participant and electrophysiologist preference . The same study also found participants with higher levels of anxiety and depression to have more AF recurrence at follow‐up after CPVA .…”
Section: Discussionmentioning
confidence: 93%
“…Mohanty et al and Yu et al both assessed improvement in depression and anxiety in patients undergoing catheter ablation [36, 37]. Mohanty et al reported that successful ablation had greater improvement in the Hospital Anxiety and depression scale and BDI scores, whereas the STAI scores did not show any association with ablation success [36].…”
Section: Resultsmentioning
confidence: 99%
“…Mohanty et al reported that successful ablation had greater improvement in the Hospital Anxiety and depression scale and BDI scores, whereas the STAI scores did not show any association with ablation success [36]. Yu et al also noted that depression and anxiety increases the recurrence risk of persistent AF after circumferential pulmonary vein ablation [37]. …”
Section: Resultsmentioning
confidence: 99%